RANCANG BANGUN MESIN PELEBUR LIMBAH PLASTIK MENJADI PAVING BLOCK BERBAHAN DASAR PLASTIK LDPE - Sukma, Hendri; Risdamaji, Ardifan; Akbar, M. Fajri (Jurnal Vokasi Indonesia, 2020)
The design of smelting and paving block molding machines made from LDPE (Low Density Polyethylene) plastic waste aims to recycle plastic waste by melting it and then reprinting it into used products and is expected to be a solution in the increasing plastic waste recycling process. The design of this smelter uses a mixer system consisting of 4 blades to facilitate the melting process of plastic waste. The planning of this machine is to use a 1 HP (Horsepower) of AC (Alternating Current) electric motor with a rotation speed of 1330 RPM (Radian per Minute). The rotation of the electric motor is then reduced to 532 RPM (Radian per Minute) during the stirring process. The components in this plastic waste melting machine consist of components that are purchased and some are produced. The components that are made include a mixer or mixer, melting tube, and machine support frame. The final result of this machine is in the form of melted plastic which has been mixed with oil and then printed in a paving block mold.